THE EFFECT OF STYLES OF LEADERSHIP AND ORGANIZATIONAL CULTURE TO WORK SATISFACTION WITH FINANCIAL PERFORMANCE - Lia Delima; M. Khusni Mubarrok; Agus Sukoco; Joko Suyono; Sriwiwoho Mudjanarko (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this study is toanalyze determine the effect of leadership style and organizational culture on job satisfaction that impact on financial performance of LembagaPengjkreditanDesa (LPD) in Bandung regency. Method, Dataobtained from 5 LPD and use 244 respondents with purposive sampling technique and collection was done using questionnaires.The analytical technique used is Structural Equation Modeling (SEM) and tested with SPSS 24 application. Result, Result of this study is leadership style have positive effect to job satisfaction and financial performance, organizational culture have positive effect to job satisfaction but have negative effect to financial performance, while job satisfaction as intervening variable have positive effect to finance. The findings of this study are for suggestions that can be given is to the village credit institutions expected to pay more attention to employees to the creation of job satisfaction so that will realize the purpose of the LPD. In addition, the leadership of the LPD also pay more attention to the pattern of action or style of leadership. With strong leadership style applied and supported by good organizational culture, it will improve company performance.s Keywords: Organizational Culture, Leadership Style, Job Satisfaction, Financial Performance.